2015
DOI: 10.1037/a0037659
|View full text |Cite
|
Sign up to set email alerts
|

Using client outcome monitoring as a tool for supervision.

Abstract: A large body of research has supported the use of client outcome monitoring and client feedback in psychotherapy. However, discussions between supervisors and trainee clinicians in supervision are still largely based on subjective appraisals made by the trainees. In this article, we discuss 3 strategies for integrating client outcome data and feedback into the supervisory process: training students to obtain and use objective client feedback, using specific client data to inform discussions of clients, and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Conversely, the data highlighted that supervisors who perceived themselves as competent and engaged with the STIC were more likely to bring the data to the supervision discussion, which resulted in increased trainee engagement. These findings support the recommendation of Swift and colleagues () that supervisors adopt client outcome measures into their clinical practice prior to shifting to outcome informed supervision. The benefits of this extended to the client system, as engaged and motivated trainees were more successful at gaining client compliance in using the STIC as a part of treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Conversely, the data highlighted that supervisors who perceived themselves as competent and engaged with the STIC were more likely to bring the data to the supervision discussion, which resulted in increased trainee engagement. These findings support the recommendation of Swift and colleagues () that supervisors adopt client outcome measures into their clinical practice prior to shifting to outcome informed supervision. The benefits of this extended to the client system, as engaged and motivated trainees were more successful at gaining client compliance in using the STIC as a part of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…To address this deficit in the training system, training protocols were developed to focus specifically on how to use the STIC in supervision. Swift et al (2014) identified three ways that client feedback can be integrated into the supervision process, namely: train students to obtain and use client feedback; use specific client feedback data to inform supervision discussions; and identify outcome patterns among supervisees' clients. Supervisor training focused on developing supervisors' ability to accomplish these three tasks could help facilitate the integration of client feedback into supervision.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy our supervisor used to address these limitations was to examine clients' session-to-session progress in a spaghetti plot 2 . By regularly examining this graphical depiction of clients' pre-specified treatment targets during supervision (Figure 1), we could determine quickly and collaboratively which trajectories indicated progress, stability, or deterioration (Swift et al, 2015) -information that facilitated effective use of limited supervision time. A substantial body of research suggests that tracking and receiving feedback on client progress may reduce the percentage of clients who ultimately deteriorate by 15% and improve the percentage of clients who ultimately recover by 30% (Lambert, 2017).…”
Section: Feedback On Client Progressmentioning
confidence: 99%
“…Another benefit of ROM software is the ability to easily aggregate outcome data by trainees. This allows supervisors to see the empirical ‘big picture’ of their supervisees’ clinical work, which could possibly constitute the most pure form of evidence-based supervision possible (Swift et al 2015). For example, at the end of each semester, supervisors can ask their trainees to create a spreadsheet which includes all of the trainees’ clients’ demographic data (e.g.…”
Section: Software For Rommentioning
confidence: 99%
“…The software features an algorithm that provides alerts for cases with higher chances of clinical deterioration (Locke et al 2012). At the end of the training year, supervisors and trainees can review their overall aggregate outcomes to see a ‘big picture’ view of their clinical work, from a quantitative perspective (Swift et al 2015).…”
Section: Technology For Evidence-based Supervision: An Example Of Usementioning
confidence: 99%